Effects of Commercial Antioxidants on Aging Resistances of Asphalt Binders - Xijie An; Ying Gao; Zizhen Dong; Qinglin Guo; Lili Li; Yancang Li (Advances in Materials Science and Engineering)
Asphalt aging has a direct influence on the durability of asphalt mixture. In order to improve thermal oxidizing aging resistance of asphalt, the commercial antioxidants including Irganox 1010 and Irgafos 168 were selected to modify base asphalt and SBR asphalt. The basic properties of modified asphalt before and after the rolling thin film oven test (RTFOT) are evaluated by penetration, softening point, ductility, and viscosity. The Fourier transform infrared spectroscopy (FTIR) test was applied to determine the antiaging mechanism of modified and unmodified asphalt. According to the test result, Irganox 1010 not only reduces the aging degree of asphalt but also has little adverse effect on other properties. Irgafos 168 with a content of 1% improves the low temperature ductility of asphalt and improves the antiaging performance of asphalt significantly. After RTFOT, the content of oxygen-containing functional groups (carbonyl group and sulfoxide group) declines significantly in antioxidation modified asphalt, and Irganox 1010 and Irgafos 168 inhibit oxidizing reaction in the aging procedure. This study can provide a useful reference for improving the aging property of asphalt in highway construction.